Decellularization of human donor aortic and pulmonary valved conduits using low concentration sodium dodecyl sulfate. (12th May 2017) - Vafaee, Tayyebeh; Thomas, Daniel; Desai, Amisha; Jennings, Louise M.; Berry, Helen; Rooney, Paul; Kearney, John; Fisher, John; Ingham, Eileen
Abstract: The clinical use of decellularized cardiac valve allografts is increasing. Long‐term data will be required to determine whether they outperform conventional cryopreserved allografts. Valves decellularized using different processes may show varied long‐term outcomes. It is therefore important to understand the effects of specific decellularization technologies on the characteristics of donor heart valves. Human cryopreserved aortic and pulmonary valved conduits were decellularized using hypotonic buffer, 0.1% (w/v) sodium dodecyl sulfate and nuclease digestion. The decellularized tissues were compared to cellular cryopreserved valve tissues using histology, immunohistochemistry, quantitation of total deoxyribose nucleic acid, collagen and glycosaminoglycan content, in vitro cytotoxicity assays, uniaxial tensile testing and subcutaneous implantation in mice. The decellularized tissues showed no histological evidence of cells or cell remnants and >97% deoxyribose nucleic acid removal in all regions (arterial wall, muscle, leaflet and junction). The decellularized tissues retained collagen IV and von Willebrand factor staining with some loss of fibronectin, laminin and chondroitin sulfate staining. There was an absence of major histocompatibility complex Class I staining in decellularized pulmonary valve tissues, with only residual staining in isolated areas of decellularized aortic valve tissues. The collagen content of the tissues was not decreased following decellularization however the glycosaminoglycan content was reduced. Only moderate changes in the maximum load to failure of the tissues were recorded postdecellularization. The decellularized tissues were noncytotoxic in vitro, and were biocompatible in vivo in a mouse subcutaneous implant model. The decellularization process will now be translated into a good manufacturing practices‐compatible process for donor cryopreserved valves with a view to future clinical use. Copyright © 2016 The Authors Tissue Engineering and Regenerative Medicine published by John Wiley & Sons, Ltd.